Towards grassroots sustainable development using human centered design and participatory rural appraisal: A study in two rural Indian villages - Krishnendu S; Hitarth Anand Rohra; Kanakasabapathy P; Krishna Nandanan; Vinod V.T Padil (Sustainable Futures)
Sustainable development in rural India is imperative for addressing the complex challenges faced by local communities while ensuring the well-being of current and future generations. However, there is a lack of a holistic multi-stakeholder participatory approach capable of identifying and effectively solving interconnected grassroots sustainability challenges of rural India. Hence, the study developed an Integrated Human-Centered Design (HCD)-Participatory Rural Appraisal (PRA) Framework which adopts a multidisciplinary bottom-up approach. The Framework was instrumental in identifying the complex socio-economic and environmental challenges battering two rural Indian villages, Ambewadi and Bhandravali, situated in the Bhor tehsil of Pune district, Maharashtra, India, precedent to the devise of solutions to offset the communal challenges. Key findings highlighted issues pertinent to inadequate healthcare facilities, irrigation water scarcity, low level literacy, waste management, and sanitary hygiene. Tackling these challenges head-on mandated multifaceted interventions - education initiatives, healthcare infrastructure investments, sustainable farming practices, and sanitation infrastructure development. This paper's investigation underscored the exigence of localized, community-driven solutions in the advocacy of sustainable rural development. By engaging stakeholders and implementing targeted interventions, the villages can progress towards sustainable growth, enhanced well-being, and resilience. The study emphasized collaborative efforts among governmental agencies, community leaders, and stakeholders to uphold lasting and impactful change, guided by insights drawn from the participatory research process for sustainable development.